The Effect of Nature Based Learning Model On The Computational Thinking of Early Childhood - Fakhita Indira Haris; Rita Mariyana; Badru Zaman (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Computational thinking has become an essential competency in 21st-century education, yet its integration into early childhood learning remains limited. This study aimed to examine the effect of the nature based learning model on the computational thinking abilities of children aged 5–6 years. A quantitative approach with a quasi-experimental, non-equivalent control group design was employed involving 32 children selected through purposive sampling. Data were collected using performance-based assessments, observation, and documentation, and analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results revealed a significant improvement in children's computational thinking following the intervention (Z = −3.563, p = .007). These findings indicate that the nature based learning model effectively promotes computational thinking through authentic learning experiences and may serve as an alternative instructional approach for strengthening 21st-century skills in early childhood education